Total synthesis and antimicrobial evaluation of xylapeptide A. (23rd August 2022) - Muchlis, Handi Nugraha; Kurnia, Dessy Yulyani; Maharani, Rani; Zainuddin, Achmad; Harneti, Desi; Nurlelasari,; Mayanti, Tri; Farabi, Kindi; Hidayat, Ace Tatang; Supratman, Unang
Abstract: Xylapeptide A is a cyclopentapeptide, [cyclo‐D‐Ala‐L‐Val‐ N ‐Me‐L‐Phe‐L‐Pip‐L‐Leu], first isolated from Xylaria sp. × Sophora tonkinensis, together with its analogue, xylapeptide B, which differ by only one residue, proline in xylapeptide B is replaced by pipecolinic acid (Pip) in xylapeptide A. Both xylapeptides A and B possess antimicrobial properties against several bacteria and fungi. Herein, we describe the first total synthesis and antimicrobial evaluation of xylapeptide A containing two non‐proteinogenic residues, N ‐Me‐phenylalanine and pipecolinic acid. The synthesis of xylapeptide A was achieved by a combination of solid‐ and solution‐phase methods that were applied for the synthesis of xylapeptide B. Interestingly, the cyclization of linear xylapeptide A was more straightforward yielding 22% compared to 8.9% for xylapeptide B, suggesting that the presence of pipecolinic acid in the linear precursor affected the cyclization process. NMR analysis of synthetic xylapeptide A revealed that the chemical shifts of all protons and carbons of xylapeptide A are highly similar to the natural product. The synthetic xylapeptide A, together with xylapeptide B, were evaluated for their antimicrobial properties, showing that synthetic xylapeptide A has moderate antimicrobial activity and better antimicrobial properties compared to synthetic xylapeptide B. The presence of pipecolinic acid in xylapeptide A is an important requirement for antimicrobial activity. Abstract : Xylapeptide A was successfully synthesized through a combination of solid‐ and solution‐phase peptide synthesis. The presence of pipecolinic acid in linear precursor facilitates the cyclization step to form cyclopeptide.